USING PARTNER READING STRATEGY TO IMPROVE READING COMPREHENSION OF GRADE EIGHT STUDENTS AT SMPN 2 TANANTOVEA - Islami, Dian; Mukrim, Mukrim; Wahyudin, Wahyudin (e-Journal of ELTS (English Language Teaching Society), 2024)
The objective of the research is to determine if using Partner Reading Strategy can improve reading comprehension of grade eight students of SMPN 2 Tanantovea. This research was conducted through a quasi experimental research design in which the sample of the research was selected using a simple random sampling technique. This research used a reading comprehension test as the instrument. The data collection of this research were analyzed statistically in order to find out the significant difference between two groups on the posttest after the treatment using Partner Reading Strategy given to the experimental group. It was found that the mean scores of both the experimental and control groups on the posttest were respectively 70 and 42. Furthermore, referring to the ttable value of df 44 (23+23-2) by applying 0.05 level of significance on one-tailed test, it was found that the tcounted value of this research (16) was higher than the ttable value (1.7). It implies that using Partner Reading Strategy can improve reading comprehension of grade eight students of SMPN 2 Tanantovea